Calculation method of underwater acoustic and vibration response of cabin segment based on onshore vibration test - Guangsheng LI; Meixia CHEN; Chunhui YUAN (Zhongguo Jianchuan Yanjiu, 2022)
ObjectiveThis paper proposes a method for calculating the acoustic and vibration response of underwater cylindrical shell structures based on land-based vibration test results.MethodsAn axisymmetric boundary element method (BEM) is introduced to describe the radiation acoustic field of the shell. The relationship of acoustic pressure at the nodal point of the generatrix with velocity is obtained by solving the numerical solution of the boundary element integral equation, then the acoustic radiation impedance matrix of the outer surface of the shell and acoustic transfer vector (ATV) are constructed. Based on the assumption that the low-order vibration mode of an underwater cylindrical shell is the same as that of an onshore cylindrical shell, combined with the modes and acoustic radiation impedance matrix of an onshore cylindrical shell, the modal added mass and damping are calculated. ResultsThe natural frequency calculation formula of the underwater cylindrical shell is established on the basis of the onshore mode, and the calculation method of underwater vibration response and acoustic radiation characteristics with the vibration response in air as input is obtained based on mode superposition method.ConclusionThe numerical results of a typical cylindrical shell with internal structure show that the method meets the engineering accuracy requirements.